Effects of CW-FIT on Teachers' Ratings of Elementary School Students at Risk for Emotional and Behavioral Disorders. (April 2018) - Caldarella, Paul; Larsen, Ross A. A.; Williams, Leslie; Wills, Howard; Kamps, Debra; Wehby, Joseph H.
Students with deficits in social skills have been found to experience both short- and long-term problems, including interpersonal conflicts and academic difficulties. These problems are compounded for students with emotional and behavioral disorders (EBD). Classwide function-related intervention teams (CW-FIT), a multitiered classroom management program, has been shown to be effective in increasing on-task behavior and decreasing disruptive behavior of students at risk for EBD. The present study examined the effects of CW-FIT on teachers' ratings of students' social skills, problem behaviors, and academic competence. A randomized control trial was completed with 160 elementary school teachers located in 19 schools across three states. Teachers completed rating scales on 350 students identified as at risk for EBD, for whom consent had been obtained. After being randomly assigned to treatment or control conditions, CW-FIT was implemented for approximately 4 months in treatment classrooms, after which teachers completed posttest ratings on all students. CW-FIT implementation was associated with significantly improved teacher ratings of social skills and academic competence for students at risk for EBD, but no significant changes in teacher ratings of student problem behaviors were found. Higher fidelity of CW-FIT implementation was associated with improved outcomes. Implications, limitations, and areas for future research are addressed.